Faktor-faktor yang mempengaruhi pengungkapan corporate social responsibility - Savitri , Inge; Pratiwi, Desy Nur; Sumadi, Sumadi (Journal of Accounting and Digital Finance, 2021)
The company makes an economic and social contribution to society in the form of corporate social responsibility (CSR). This study aims to examine the factors that influence CSR disclosure in manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2018 period. The sampling method was purposive sampling, with a sample size of 27 companies. This study uses multiple linear regression. The results showed that profitability, company growth (growth), and company size (Size) were partially related to CSR disclosure.